1999
DOI: 10.1073/pnas.96.21.11764
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of deformability at a tRNA recognition site and aminoacylation specificity

Abstract: The fidelity of protein synthesis depends on specific tRNA aminoacylation by aminoacyl-tRNA synthetase enzymes, which in turn depends on the recognition of the identity of particular nucleotides and structural features in the substrate tRNA. These features generally reside within the acceptor helix, the anticodon stemloop, and in some systems the variable pocket of the tRNA. In the alanine system, fidelity is ensured by a G⅐U wobble base pair located at the third position within the acceptor helix of alanine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In our case, we also did not observe the amino signals in the CC mismatch in both the amino optimized does not reappear at higher paromomycin concentrations, so is not merely a result of a partially occupied binding site, but signal averaging between multiple conformations or motion of the ligand in the binding site. Motion at a CC mismatch was also observed for a mutant tRNA acceptor minihelix (Chang et al 1999) and for a DNA molecule containing a CC mismatch (Boulard et al 1997). It is possible that aminoglycoside binding is linked to or enhanced by the dynamic nature of the CC mismatch.…”
Section: Discussionmentioning
confidence: 82%
“…In our case, we also did not observe the amino signals in the CC mismatch in both the amino optimized does not reappear at higher paromomycin concentrations, so is not merely a result of a partially occupied binding site, but signal averaging between multiple conformations or motion of the ligand in the binding site. Motion at a CC mismatch was also observed for a mutant tRNA acceptor minihelix (Chang et al 1999) and for a DNA molecule containing a CC mismatch (Boulard et al 1997). It is possible that aminoglycoside binding is linked to or enhanced by the dynamic nature of the CC mismatch.…”
Section: Discussionmentioning
confidence: 82%
“…It is, therefore, of utmost importance to understand and obtain an estimate of the degree of nonisostericity of nWC base pairs compared to the preponderant WC pairs. It is recognized that the presence of nWC pairs amid WC pairs influences the structure of nucleic acid duplexes, and nonequivalent base-pair substitutions are found to eliminate function (Chang et al 1999;Zhong et al 2006), thus playing a major role in the evolution of macromolecules (Gutell et al 1994). However, rationale for the observed nWC base pair-mediated mechanistic effects in RNA duplexes still remains vague.…”
Section: Discussionmentioning
confidence: 99%
“…These findings clearly indicated that the D loop-T⌿C loop tertiary interactions are required for the serylation of mt tRNA UGA Ser , whereas only the sequence of the T⌿C loop is important for the activity of mt tRNA GCU Ser . Aminoacylation of E. coli tRNA Ala by alanyl-tRNA synthetase (AlaRS) depends on a G3⅐U70 wobble base pair in the acceptor stem (37). Understanding such a unique identity determinant was greatly advanced by the demonstration that the minihelix variant, composed only of the amino acid acceptor-T⌿C helix, could be a good substrate for AlaRS (38, 39).…”
Section: Trna Gcu Ser Identity Elements For Mt Serrs-ueda Et Al (33)mentioning
confidence: 99%